PROFESIONALISME GURU MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI SD 200205 PADANGSIDIMPUAN - Maulana Arafat (IAIN Padangsidimpuan, 2019)
Teacher professionalism in not as slogan anymore, but it has become a job or activity that must be done. This research aims to describe students respond, stakeholders and headmaster of elementary school 200205 in Padangsidimpuan city toward teacher professionalism of Islamic education and character lesson. This is field research in qualitative descriptive where in this research, the researcher looks for and uses descriptive data such as words or utterance, opinions from research subject either orally or in writing. Data collections are conducted with interview and documentation method. Analysis technique is begun of data reduction, data presentation and conclusion. Data analysis is conducted while data is collected and after all data are collected or after the research is done. The result ofresearch shows that the respond of student, stakeholder and headmaster elementary school 200205 Padangsidimpuan city is good in aspect of subject mastery, learning media use, and learning strategies application. However, preparation of learning device before beginning the study need to be improved such as making annual programs, semester programs, syllabus, lesson plans, and assessmentas that stiil out of expectatios. Therefore this research is done so that teacher in Islamic education and character lesson is able to be professional educator based on competence.